Quo vadis geriatric rehabilitation? - Becker, Clemens; Achterberg, Wilco P. (Age & ageing, 2022)
The sustainability of healthcare of older people in Europe is at stake. Many experts currently focus on the COVID-19 pandemic and its consequences. But there are other elements coming up that might even have a greater impact. Healthcare systems, geriatric care and geriatric rehabilitation in particular, will face disruptive changes due to both demographic demand and a shortage of human and financial resources. This decade will be transformed by a high proportion of the older health workforce transitioning to retirement. This expertise must be retained. The brain drain of health care workers migrating from Eastern parts to Western Europe is diminishing. Discussing and deciding upon the priorities of value-based health care for older people such as equity and access is required. The acute healthcare sector in most countries focuses on fee-for-service models instead of building systemic approaches to maximise independence and autonomy of older citizens. In this commentary, we build on recent book chapters and articles on geriatric rehabililtation. Our main questions for the anniversary edition of Age and Ageing is what it is that geriatric rehabilitation could, should and must contribute in the roaring 2020s?
Gesehen am 18.07.2022